2016
DOI: 10.1186/s13613-016-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between total antioxidant capacity and mortality in ischemic stroke patients

Abstract: ObjectiveData on circulating total antioxidant capacity (TAC) levels in ischemic stroke patients compared with healthy controls are limited and provided conflicting findings. There are not data about the association between circulating TAC levels, peroxidation state and outcome in patients with severe ischemic stroke. The objective of this study was to examine the relationship of TAC with 30-day mortality after severe ischemic stroke.Methods This multicenter study included 58 patients with coma (Glasgow Coma S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 30 publications
8
25
1
1
Order By: Relevance
“…Nonetheless, a previous study found a relationship between severe malignant middle cerebral artery infarction, serum TAP levels, and 30-day mortality. 11 Similarly, another study concluded that TAP levels were more in diabetic stroke than in nondiabetic stroke patients, although we did not find any such association in our sample. 12 In a previous study, TAP has been associated with the volume of ischemic cerebral infarction and the degree of neurologic impairment.…”
Section: Discussioncontrasting
confidence: 81%
“…Nonetheless, a previous study found a relationship between severe malignant middle cerebral artery infarction, serum TAP levels, and 30-day mortality. 11 Similarly, another study concluded that TAP levels were more in diabetic stroke than in nondiabetic stroke patients, although we did not find any such association in our sample. 12 In a previous study, TAP has been associated with the volume of ischemic cerebral infarction and the degree of neurologic impairment.…”
Section: Discussioncontrasting
confidence: 81%
“…The brain is exceedingly vulnerable to oxidative stress, due to a consumption of 20% of body oxygen, relatively high concentrations of iron content and readily peroxidizable lipids, as well as comparatively insufficient antioxidant defences 24 . Additionally, several clinical studies have shown elevated 8-OHdG and MDA are both markers of ischaemic brain injury and clinical outcome of ischaemic stroke 10 , 26 . Moreover, Brea et al .…”
Section: Discussionmentioning
confidence: 99%
“…8-hydroxydeoxyquanosine (8-OHdG) and malondialdehyde (MDA) are common end-products of deoxyribonucleic acid (DNA) oxidation and lipid peroxidation, respectively, and can be detected in body fluid or brain in humans 8 . The systemic oxidative stress response to acute ischaemic stroke involves increases in 8-OHdG and MDA, which have also been associated with poor functional recovery 9 and mortality 10 . While higher peripheral blood levels of 8-OHdG 11 and MDA 12 have been associated with dementia, and some researchers have found that oxidative stress is related to cognition, without dementia or stroke 13 , the association between 8-OHdG or MDA and PSCI has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Total antioxidant capacity (T-AOC) is an important index reflecting the body's ability to compensate for excess free radicals via the antioxidant system, the state of free radical metabolism in the body, and the body's antioxidant function. Higher serum T-AOC levels are associated with mortality in patients with severe ischemic stroke and could be used as a prognostic biomarker (Lorente et al, 2016). T-AOC includes both enzymatic and non-enzymatic systems.…”
Section: Enzymatic and Non-enzymatic Antioxidant Systemsmentioning
confidence: 99%